2015
DOI: 10.1039/c5cc03676c
|View full text |Cite
|
Sign up to set email alerts
|

P(NMe2)3-mediated reductive [1+4] annulation of isatins with enones: a facile synthesis of spirooxindole-dihydrofurans

Abstract: A novel P(NMe2)3-mediated reductive [1+4] annulation reaction between isatins and enones has been developed, providing the facile synthesis of spirooxindole-dihydrofurans. This reaction unveils the first practical approach to construct five-membered cyclic motifs via a Kukhtin-Ramirez adduct involved [1+4] annulation mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…For this study, we chose to utilize a Kukhtin–Ramirez ‐like redox neutral condensation to exploit the biphilic nature of oxyphosphonium enolates as C 1 subunits . Recent work by Radosevich , He , and our own group have demonstrated the versatility of this approach in providing direct access to C−C and C−X bonds …”
Section: Introductionmentioning
confidence: 99%
“…For this study, we chose to utilize a Kukhtin–Ramirez ‐like redox neutral condensation to exploit the biphilic nature of oxyphosphonium enolates as C 1 subunits . Recent work by Radosevich , He , and our own group have demonstrated the versatility of this approach in providing direct access to C−C and C−X bonds …”
Section: Introductionmentioning
confidence: 99%
“…The in situ-generated Kukhtin-Ramirez adduct from 4a and P(NMe 2 ) 3 acts as the basic catalyst. [11][12][13] On the basis of the above mechanistic investigations and closely related reports from our group and others, [7][8][9] ap roposed mechanism to account for the formation of 3 or 6 is depicted in Scheme4.P resumably,t he reaction is initiated by formation of the Kukhtin-Ramirez adduct A from isatin 1 or a-keto ester 4 and P(NMe 2 ) 3 . [5] Through its dipolar form B, the Kukhtin-Ramirez adduct subsequentlye ngages in aM ichael addition to diene 2,a ffording the intermediate C,w hich then undergoes as terically favored intramolecular substitutionv ia its allylic carbanion form C1 to give the vinylcyclopropane intermediate 5.…”
mentioning
confidence: 97%
“…[8] Aside from [1+ +2] annulation reactions, we also demonstrated that Kukhtin-Ramirez adducts can undergo [1+ +4] annulation with enones,a ffording af acile synthesis of dihydrofurans (Scheme 1b). [9] These annulation reactions originate from the characteristic reactivity of Kukhtin-Ramirez adducts as 1,1-dipoles and presumably proceed through aM ichael addition-intramolecular substitution sequence.…”
mentioning
confidence: 99%
See 2 more Smart Citations